“I still hope it’s just a blip”: constructing life with dementia in a public digital health community - Pleyer, Monika (Discourse, context & media, 2025)
This study aims to provide insights into how people living with the condition metaphorically construe dementia as well as themselves in the virtual discourse environment of a digital health community. Offline constructions of dementia in the media mostly do not include the perspectives of those diagnosed, instead centring dehumanising ‘panic-blame’ discourses. This paper seeks to address this shortcoming and places persons with the condition centre stage in a critical conceptual metaphor analysis of selected relevant threads from the “I have dementia” subforum of the “Dementia Support Forum” (Alzheimer’s Society UK).11https://forum.alzheimers.org.uk/. In a qualitative, data-driven, bottom-up approach the study shows that key metaphors from the mass media are largely absent in discourses of persons diagnosed. In the subforum, negative metaphorical constructions do not highlight dementia’s impact on society, but the person’s own health conditions, as well as their practices of identity constructions in this digital CofP. Metaphors address the person themself, specifically their struggles with health and illness (dementia as a war or loss, split self), explanations of physical symptoms (bodies are machines) to self and non-diagnosed persons, as well as practices of digitally construing their identity as people living with dementia (dementia as a game or prison). While some negative construals echo those found in the media (dementia as a malevolent agent or opponent), depersonalising aspects tend to be absent; the users in turn construe themself as agentive warriors (even if they acknowledge that their agency is diminished or altered). This analysis thus highlights the relevance of metaphor analysis in a digital coping context.